Room temperature dehalogenation of (hetero)aryl halides with magnesium/methanol. Issue 32 (8th August 2018) - Jouha, Jabrane; Khouili, Mostafa; Hiebel, Marie-Aude; Guillaumet, Gérald; Suzenet, Franck
Graphical abstract: Highlights: (Hetero)aryl halides are efficiently dehalogenated with magnesium in methanol. Various functional groups are tolerated under mild conditions. Iodo-, bromo- and chloro-derivatives are good substrates. This dehalogenation method represents a trustworthy alternative to other approaches already reported. Abstract: Magnesium in methanol was found to be an effective and inexpensive reagent for the dehalogenation of (hetero)aryl chlorides, bromides and iodides under mild conditions. The halogen/hydrogen exchange proceeded at room temperature and tolerated functional groups such as esters, nitriles, alcohols, and alkenes.